2021
DOI: 10.3897/zookeys.1010.58759
|View full text |Cite
|
Sign up to set email alerts
|

Numerous new records of tropical non-indigenous species in the Eastern Mediterranean highlight the challenges of their recognition and identification

Abstract: New data on 52 non-indigenous mollusks in the Eastern Mediterranean Sea is reported. Fossarus sp. (aff. aptus sensu Blatterer 2019), Coriophora lessepsiana Albano, Bakker & Sabelli, sp. nov., Cerithiopsis sp. aff. pulvis, Joculator problematicus Albano & Steger, sp. nov., Cerithiopsis sp., Elachisina sp., Iravadia aff. elongata, Vitrinella aff. Vitrinella sp. 1 (sensu Blatterer 2019), Melanella orientalis, Parvioris aff. dilecta, Odostomia cf. dalli, Oscilla virginiae, Parthenina cossmanni, Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 113 publications
(100 reference statements)
3
26
0
Order By: Relevance
“…However, according to Zenetos et al (2018) "the contemporary presence in Astypalaia of two taxa belonging to Isognomon Lightfoot, 1786, one of which apparently absent from the Red Sea, seems unlikely", so that the same researchers preferred to ascribe both records to the Red Sea taxon I. legumen "to avoid the inflation of alien molluscan records and pending molecular confirmations". Partially in agreement with this latter opinion, Albano et al (2021) prudentially reported "I. aff. australica (sensu Angelidis and Polyzoulis, 2018)" from Cyprus and Kriti.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, according to Zenetos et al (2018) "the contemporary presence in Astypalaia of two taxa belonging to Isognomon Lightfoot, 1786, one of which apparently absent from the Red Sea, seems unlikely", so that the same researchers preferred to ascribe both records to the Red Sea taxon I. legumen "to avoid the inflation of alien molluscan records and pending molecular confirmations". Partially in agreement with this latter opinion, Albano et al (2021) prudentially reported "I. aff. australica (sensu Angelidis and Polyzoulis, 2018)" from Cyprus and Kriti.…”
Section: Introductionsupporting
confidence: 73%
“…Subsequently, an accurate sorting was carried out under a stereomicroscope, and the selected specimens definitively fixed in 70% or 95% ethanol, depending on their destination for analysis. Shell characters are investigated to propose a morphological identification comparing the shells of the new Mediterranean specimens with shells of previous works (Huber, 2010;Mienis et al, 2016;Micali et al, 2017;Ovalis & Zenetos in Stamouli et al, 2017;Angelidis & Polyzoulis, 2018;Crocetta, 2018;Giacobbe & Renda in Dragičević et al, 2019;Prato & Rubino in Kousteni et al, 2019;Scuderi & Viola, 2019;Marchini et al, 2020;Albano et al, 2021;Bini & Pinasco, 2021;Manousis et al, 2021), and pictures of shell specimens of I. bicolor (AMNH:307896) from Florida Keys (USA) and M. regula (AMNH:319335 and AMNH:319339) from Darwin Harbour, Australia stored at the American Museum of Natural History (AMNH).…”
Section: Monitoring and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we observed a considerable increase in taxonomic and functional diversity of the nonindigenous assemblage component, which drove corresponding positive trends in index values of the entire molluscan assemblage. Expected NIS richness rose by 0.55 species per year throughout the study period, consistent with ongoing introductions and the establishment of new Indo‐Pacific taxa in the region (e.g., Albano, Steger, Bakker, et al., 2021; Galil et al., 2021; Guarnieri et al., 2017). The taxonomic diversification went along with a pronounced increase in nonindigenous functional richness (correlation of NIS species richness with NIS functional richness, differenced time series: rho = .83, p < .001), as well as that of the entire regional molluscan assemblage (correlation of NIS species richness with complete assemblage functional richness, differenced time series: rho = .85, p < .001).…”
Section: Discussionsupporting
confidence: 54%
“…Distribution data on marine NIS in the Mediterranean Sea were retrieved from the European Environment Agency/Hellenic Centre for Marine Research (EEA/HCMR) offline database stored in the European Alien Species Information Network (EASIN) (https://easin.jrc.ec.europa.eu/easin (accessed on 17 November 2021)), which is continuously updated based on emerging literature regarding new occurrence/records, nomenclatural or taxonomic changes, and updates in the establishment success and alien status of species. For the purposes of this work, we took into account species records detected from 1970 until the end of 2020, and published until November 2021. Notable changes since the last major update on the Mediterranean NIS [15], in addition to new records, include the addition of Foraminifera following Stulpinaite et al [16], the revision of Isopoda following Castelló et al [17], the revision of Polychaeta following Langeneck et al [18] and the revision of Mollusca based on Albano et al [19]. Furthermore, molluscan records based exclusively on empty shells, as well as species records not in the wild, were excluded.…”
Section: Data and Definitionsmentioning
confidence: 99%